تأثير موعد وطريقة التطعيم على نجاح مطاعيم غراس العناب - دواي فيصل; اسماعيل هيثم; حمدو منال (Latakia University Journal -Biological Sciences Series, 2019)
تم تطعيم الأصناف الثلاثة ( حفاوي – مدعبل – كمثري )على الأصل الحفاوي المنتج خضرياً أوبذرياً وكانت النتائج كالتالي: 1_ لم يؤثر موعد التطعيم تأثيراً معنوياً على نسبة نجاح المطاعيم عند استخدام التطعيم اللساني في كافة المعاملات, في حين كان لموعد التطعيم أثراً على الصنف المدعبل و الحفاوي باستخدام الطريقة الروسية . 2_ بمقارنة الطرق الثلاث ( اللساني _ الروسية _ الدرعية ) تبين مايلي : تفوقت الطريقة اللسانية و البرعمة الروسية في الصنف المدعبل على البرعمة الدرعية وكانت نسب النجاح وفق التسلسل التالي : (%70 –- %88 _%96.7 ) في حين تفوقت الطريقة اللسانية في العناب الحفاوي على الطريقة الروسية وهذه بدورها تفوقت على البرعمة الدرعية وكانت نسب النجاح حسب التسلسل التالي : (%50 - %84.3 - %100 ). 3 _ أعطت طريقة البرعمة الروسية فترة زمنية أطول للقيام بعملية التطعيم مقارنة بالبرعمة الدرعية. Three species have been grafted (Hafawe-Modaabal-Komthary) on the vegetal, or seed plant rootstock. The results were as following: 1-The date of graftage, had’nt any significant effect on the ratio of success of budding in case of using Tongue-graft in all the treatments, at the time that, the date of graftage had an effect on the specie Modaabal, and Hafawe by using the Russian method. 2- Comparing the three methods (Tongue, T, B) showed: The Tongue-methods, and Russian budding (B) have been better, in the Modaabal specie than T-budding method, the ratio of success, has been according to the following succession: (96.7%- 88% - 70% ) at the time that, the tongue-method in the Hafawe zizyphus has been better than Russian budding, which had been better than t-budding, the ratio of success has been as following succession: (100% - 84.3% - 70 % ). 3-Russian method permited a longer time to the graftage operation in comparison with T-budding.